2019
DOI: 10.1128/jvi.01883-18
|View full text |Cite
|
Sign up to set email alerts
|

The Human CD4+T Cell Response against Mumps Virus Targets a Broadly Recognized Nucleoprotein Epitope

Abstract: Mumps outbreaks among vaccinated young adults stress the need for a better understanding of mumps virus (MuV)-induced immunity. Antibody responses to MuV are well characterized, but studies on T cell responses are limited. We recently isolated a MuV-specific CD4+ T cell clone by stimulating peripheral blood mononuclear cells (PBMCs) from a mumps case with the viral nucleoprotein (MuV-N). In this study, we further explored the identity and relevance of the epitope recognized by the CD4+ T cell clone and ex vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
(46 reference statements)
0
14
0
Order By: Relevance
“…Although, it has also been shown that natural mumps infection or vaccination do not always induce both cellular and humoral immunity. de Wit et al (199,236,237) has shown the presence of Th1-type CD4 + T-cells recognizing a MuV epitope in a HLR-DR restricted manner. In addition, the response of IFN-γ and TNF producing CD8 + T-cells specific to MuV epitopes are lower in vaccinated individuals when compared to individuals who were naturally infected (199,213,(236)(237)(238).…”
Section: Is Lymphoproliferative Immunity a Better Correlate Of Protection?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although, it has also been shown that natural mumps infection or vaccination do not always induce both cellular and humoral immunity. de Wit et al (199,236,237) has shown the presence of Th1-type CD4 + T-cells recognizing a MuV epitope in a HLR-DR restricted manner. In addition, the response of IFN-γ and TNF producing CD8 + T-cells specific to MuV epitopes are lower in vaccinated individuals when compared to individuals who were naturally infected (199,213,(236)(237)(238).…”
Section: Is Lymphoproliferative Immunity a Better Correlate Of Protection?mentioning
confidence: 99%
“…de Wit et al (199,236,237) has shown the presence of Th1-type CD4 + T-cells recognizing a MuV epitope in a HLR-DR restricted manner. In addition, the response of IFN-γ and TNF producing CD8 + T-cells specific to MuV epitopes are lower in vaccinated individuals when compared to individuals who were naturally infected (199,213,(236)(237)(238). Utilizing current knowledge and new technologies may help define a better surrogate correlate of protection and potentially determine a cut-off between the immunity of a vaccinated individual and a secondary mumps infection.…”
Section: Is Lymphoproliferative Immunity a Better Correlate Of Protection?mentioning
confidence: 99%
“…APIQGTNLL (V/P/I 27-35 ), KPRTSTPVTEF (V/P/I 142-152 ), IPNARANL (NP 115-122 )), each inducing a strong T cell response in expanded effector T cells obtained from three different HLA-B*07:02-positive mumps patients. Interestingly, the first described MuV-specific CD4 + T-helper cell epitope, GTYRLIPNARANLTA (NP 110-124 ), which we recently discovered 18 , contains the newly identified HLA-B*07:02-restricted CD8 + T cell epitope IPNARANL (NP 115-122 ). This opens the possibility of using synthetic peptides, containing both epitope sequences, to stimulate CD4 + and CD8 + T cell responses simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…A flow cytometry-based killing assay was used to determine the cytotoxic capacity of the various epitope-specific T cell lines 18 . For this purpose, BLCL as antigen-presenting cells were labeled with 0.1 µM CellTrace violet (C34557, Thermo Fisher Scientific) and pulsed with one of the five selected peptides (5 µM) or medium or non-immunogenic MuV peptide as negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of T cell epitopes can be a useful tool to characterize the CD8 + T cell response after vaccination, and explore the cross-reactive potency of the T cells induced by vaccination towards circulating strains. Recently, we described the first set of T cell epitopes of MuV [ 16 , 17 ]. CD8 + T cell epitopes of MuV were identified by eluting peptides from HLA Class I (HLA-I) molecules from antigen-presenting cells that were infected with MuV, using a genotype G outbreak strain.…”
Section: Introductionmentioning
confidence: 99%